CRC handbook of chemistry and physics : a ready-reference book of chemical and physical data - Haynes, William M.; Lide, David R., 1928- (CRC Press/Taylor & Francis, 2011)
Mirroring the growth and direction of science for a century, the CRC Handbook of Chemistry and Physics, now in its 92nd edition, continues to be the most accessed and respected scientific reference in the world, used by students and Nobel Laureates. The benchmark of scientific reference since the days of Einstein, Eddington, and Planck, no book is held to a higher standard than the Handbook of Chemistry and Physics. Perpetually vetted for misspellings, miscalculations, misperceptions, and misnomers, it is republished every year, so no mistake needs to be long abided, no enhancement long awaited.